2007
DOI: 10.1007/s10578-007-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress as a Predictor of Age Upon Admission to a Child Psychiatric Inpatient Facility

Abstract: The current study examined child symptoms and parenting stress as predictors of children's age upon admission to a psychiatric inpatient facility. The children (N = 252) ranged from 6 to 12 years of age; most were male (71%) and over half were African American (59%). Externalizing behavior symptoms were associated with a younger age upon admission and internalizing behavior symptoms were associated with an older age. Parental social isolation was associated with a younger child's age upon admission, whereas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…From a theoretical standpoint, these findings are consistent with research that has suggested that the high degree of comorbidity between anxiety and depression is due to a common, underlying construct, alternately referred to as internalizing, general distress, or negative affect [48, 70]. This internalizing factor is consistent with research that has implicated a broad internalizing or general-distress construct underlying anxiety, depression, and to a lesser extent, substance-use disorders in adults and children [44, 45]. The results also suggest that there remains significant value in conceptualizing the anxiety and depressive disorders as separate constructs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From a theoretical standpoint, these findings are consistent with research that has suggested that the high degree of comorbidity between anxiety and depression is due to a common, underlying construct, alternately referred to as internalizing, general distress, or negative affect [48, 70]. This internalizing factor is consistent with research that has implicated a broad internalizing or general-distress construct underlying anxiety, depression, and to a lesser extent, substance-use disorders in adults and children [44, 45]. The results also suggest that there remains significant value in conceptualizing the anxiety and depressive disorders as separate constructs.…”
Section: Discussionsupporting
confidence: 86%
“…Broad internalizing symptoms are well documented in youth [cf. 44], and their measurement shows clinical utility [i.e., 45]. Indeed, higher order structures have been called upon to explain covariation among anxiety disorders and between anxiety and depressive disorders [i.e., 46, 47, 48].…”
Section: Introductionmentioning
confidence: 99%
“…The Total Parenting Stress score also demonstrated incremental validity as evidenced by its ability to predict parent self-efficacy and parent empowerment over and above the effect of family functioning (Scheel & Rieckmann, 1998). In addition, the PSI Attachment subscale score significantly predicted child levels of narcissism and callous/unemotional traits above and beyond child aggression levels (Fite, Stoppelbein, & Greening, 2008). The PSI demonstrated excellent treatment sensitivity as Total Parenting Stress and child and parent domain scores decreased following various forms of intervention (e.g., parent training, problem solving training, parent-child interaction therapy).…”
Section: Resultsmentioning
confidence: 90%
“…The PSI is the most widely used measure of parenting stress in parents of young children with a variety of health, developmental and behavioral problems (e.g., Brummelte et al, 2011; Collett, Cloonan, Speltz, Anderka, & Werler, 2012; Faught, Bierl, Barton, & Kemp, 2007; Fite, Stoppelbein, & Greening, 2008; Glenn, Cunningham, Poole, Reeves, & Weindling, 2009; Tu et al, 2007; Webster, Majnemer, Platt, & Shevell, 2008). The PSI long form contains 120 items comprising three domains: Child Domain, Parent Domain, and Life Stress Domain.…”
Section: Methodsmentioning
confidence: 99%